Improving the performance of water delivery systems in the Dez and Moghan irrigation schemes in Iran - Hedayat, Najaf (Cranfield University, 2005)
Despite the importance of efficient irrigation management for sustainable agriculture in semi-arid and arid regions of the world, poor water delivery is widespread. Following recent rural reforms in Iran, which have changed the land holding regime, cropping pattern, and market system, the present canal management is no longer responsive to the new challenges of farmers in irrigation schemes such as the Dez and Moghan. This research aims to identify an appropriate canal management model for improving water delivery, using the stakeholders’ own views and understanding of the local issues. After reviewing the literature, four expert workshops were organized to identify important issues. A postal survey of 100 farmers, 50 extensionists and 50 water agency staff was then undertaken. This was then augmented by 36 semi-structured and open-ended interviews with stakeholders not covered by the survey. The majority of all three-stakeholder groups agreed that present canal management in both the schemes is not appropriate and causes various problems, but they did not agree on the causes of the problems. The majority view among the farmers and extensionists was that inequity and inflexibility, due to poor operation and maintenance (O&M) of the main and secondary canals, were the most important causes of poor water delivery. In contrast, the agency staff regarded group conflicts and environmental impacts, due to poor O&M in the tertiaries and quaternaries and poor on-farm operations, as the most important. The perceptions of the stakeholders on water delivery-related issues were similar on the two schemes. The farmers and extensionists had similar views on all issues except on water charges, where the extensionists (agreeing with the agency staff) suggested that present charges were too low to reflect the O&M costs. In contrast, the farmers thought that higher charges alone would not help, because the problems lie with poor design and the present inappropriate management system. The farmers and extensionists thought that neither purely technical nor purely nontechnical approaches alone would be adequate to resolve the problems. They supported an integrated management model, based on the traditional Iranian Miraab system. Although the survey responses suggested that all three-stakeholder groups would support this, the interviews suggested that majority of the farmers and extensionists thought some of the agency staff would resist its implementation because the farmer managed water distribution system would be seen to be a threat to their authority. All three groups thought that the government would support the implementation of the Miraab system. The key implications of the research is that the stakeholders consider the present management of the Dez and Moghan schemes is not responsive to the challenges in the post-reform era, and that they are more likely to be met by a system that is based on a bottom-up approach rather than one that is imposed by the state agencies. They consider that the governments are not always the best resource manager, and that a farmer managed water distribution system (e.g. the Miraabs) could do a better job. The research confirmed the importance of consulting different stakeholder groups, who might have different attitudes and perceptions of the problems and potential solutions.
Keywords: Dez; Moghan; irrigation water delivery; O&M; water charges; Miraab system; Qanat